2009
DOI: 10.1097/eja.0b013e328328f662
|View full text |Cite
|
Sign up to set email alerts
|

Forced-air warming effectively prevents midazolam-induced core hypothermia in volunteers

Abstract: We conclude that forced-air warming can effectively prevent midazolam-induced redistribution hypothermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
3
7
3
Order By: Relevance
“…This seems especially true, if this drop in core temperature, as we have shown in our study, cannot be offset by active prewarming. This result is in contrast to the findings of Sato et al [12] who observed that prewarming did not prevent a transient decrease in core temperature by midazolam, but increased the temperature to the control level thereafter. However, in our study active prewarming was started about 40 min after premedication and not at the time of premedication.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This seems especially true, if this drop in core temperature, as we have shown in our study, cannot be offset by active prewarming. This result is in contrast to the findings of Sato et al [12] who observed that prewarming did not prevent a transient decrease in core temperature by midazolam, but increased the temperature to the control level thereafter. However, in our study active prewarming was started about 40 min after premedication and not at the time of premedication.…”
Section: Discussioncontrasting
confidence: 99%
“…In another study administration of 0.075 mg.kg − 1 midazolam i.m. was also associated with a drop of core temperature of 0.5 °C [12]. These results are comparable to the results of our study in which core temperature dropped 0.3 °C between administration of flunitrazepam and induction of anaesthesia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The increase in body temperature in the FAW group should be considered modest. It is similar to those arising from testing of this intervention with sedated patients in controlled experimental conditions 16 and with application of active warming during neuraxial anaesthesia. 17 A recent meta-analysis of eight trials with 1189 participants who received neuraxial anaesthesia found that active warming increased postoperative temperature by 0.36°C in comparison with passive warming (95% CI=0.16 to 0.55) and reduced risk of hypothermia by 29% (RR 0.71, 95% CI=0.61 to 0.83).…”
Section: Discussionmentioning
confidence: 52%
“…[27] The reasons for this may include the short length of the operations involved in this study and the different types of patients recruited, surgeries performed, and precise methods of rewarming selected. [28] …”
Section: Discussionmentioning
confidence: 99%